Digital Media Intensity and Adolescent Religiosity: Integrating Social Media as Educational Da’wah in Islamic Secondary Education - Obadare, Babatunde; Rahman, Mohamed Abdel; Mūgambi, Jesse Ndwiga Kanyua (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to examine the influence of digital media intensity on adolescent religiosity and to analyze how social media can be integrated as an educational da’wah instrument within Islamic secondary education to strengthen students’ multidimensional religiosity. Methodology: This study employed a mixed-method sequential explanatory design. Quantitative data were collected using a five-point Likert-scale questionnaire measuring religiosity and digital media intensity, distributed to 175 students. Data were analyzed using SPSS through descriptive statistics, Kolmogorov–Smirnov normality test, Pearson correlation, and simple linear regression. Qualitative data were obtained through interviews. Main Findings: The results indicate that students’ overall religiosity is categorized as moderate high, while digital media intensity is high. Pearson correlation analysis shows a moderate positive correlation (r = 0.436, p < 0.05). Regression analysis reveals that digital media intensity significantly predicts religiosity, explaining 19% of its variance, while 81% is influenced by other factors. Novelty/Originality of this study: This study reframes digital media from a perceived moral risk into a strategic educational da’wah instrument within Islamic schools. By integrating multidimensional religiosity theory, digital engagement intensity, and school-based pedagogical intervention through a mixed-method design, it provides a new integrative framework for understanding adolescent religiosity in the digital era.